2001
DOI: 10.1100/tsw.2001.358
|View full text |Cite
|
Sign up to set email alerts
|

The Current Status of Microscopical Hair Comparisons

Abstract: Although the microscopical comparison of human hairs has been accepted in courts of law for over a century, recent advances in DNA technology have called this type of forensic examination into question. In a number of cases, post-conviction DNA testing has exonerated defendants who were convicted in part on the results of microscopical hair comparisons. A federal judge has held a Daubert hearing on the microscopical comparison of human hairs and has concluded that this type of examination does not meet the cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Nevertheless, the search for more objective criteria by which to judge hair matches continues ( Taupin, 2004 ). Hair evidence is ordinarily supplemented by DNA evidence whenever possible ( Rowe, 2001 ). When follicle tissue is present, nuclear DNA extracted from a hair sample may identify the donor.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the search for more objective criteria by which to judge hair matches continues ( Taupin, 2004 ). Hair evidence is ordinarily supplemented by DNA evidence whenever possible ( Rowe, 2001 ). When follicle tissue is present, nuclear DNA extracted from a hair sample may identify the donor.…”
Section: Discussionmentioning
confidence: 99%
“…Within a family or genus, it is difficult to successfully discriminate species by means of only a single medullar or cuticular scale pattern. Wildlife forensic medicine has been working on discriminating animal hair using multivariate morphological function to improve discriminant accuracy (Oli 1993, Rowe 2001, Anwar et al 2011, Kerley et al 2015. Sato et al (2006) obtained a discriminant rate of 96% and 99% for cat hair and dog hair, respectively, with 13 hair parameters.…”
Section: Application Of Hair Quantitative Morphological Characteristicsmentioning
confidence: 99%
“…* discriminate species by means of only a single medullar or cuticular scale pattern. Wildlife forensic medicine has been working on discriminating animal hair using multivariate morphological function to improve discriminant accuracy(Oli 1993, Rowe 2001, Anwar et al 2011, Kerley et al 2015.Sato et al (…”
mentioning
confidence: 99%
“…Furthermore, Smith confi rmed that the hairs taken from the wooden portion of the axe matched 'in all details' to the sample taken from the victim; these would have been compared microscopically to identify similarities in colour, structure and cuticular traits between the hair taken from the axe to those taken from the victim. 19 A reconstruction of the skull was also undertaken by Smith, and in his evidence he notes that signifi cant cracking and shattering of the bone was observable. When questioned further Smith acknowledged that the resultant injuries would have been caused by some considerable force and that the reconstruction of the skull showed that the axe fi tted exactly with the injuries.…”
Section: The Materials Culture Of Forensic Investigationsmentioning
confidence: 99%
“…12 Marr was arrested for the murder of his colleague Mary Ann Mills who was found dead at their place of occupation, a framing workshop on Rose Street, Edinburgh. Short articles covering the trial of this case were identifi ed in The Scotsman, 19 February 1929, and The Aberdeen Press and Journal, 20 February 1929, but a second article in The Scotsman, 20 February 1929, provides the greatest detail of the evidence given. The article indicates a plea of insanity was put forth by the defendant and outlines the evidence provided in support of this.…”
Section: The Materials Culture Of Forensic Investigationsmentioning
confidence: 99%